The Influence of Social Change on Human Resource Management Strategies in the Digital Era - Paulus Robert Tuerah,; Manuel E. Korompis,; Grystin Djein Sumilat,; Nismawati,; Eric Kondoy, (Technium Education and Humanities, 2024)
Social change in the digital era has had a significant impact on various aspects of life, including the world of work and human resource management (HR). This study aims to explore the influence of social change on HR management strategies in the digital era, as well as identify the challenges and opportunities that arise in the process of organizational adaptation. Using a qualitative approach and literature review method, this study analyzes the latest scientific literature from various trusted sources, including academic journals, textbooks, and industry reports. The results of the study indicate that social change has driven transformation in various aspects of HR management, including recruitment, retention, employee development, performance management, and organizational culture. Digitalization, shifting workforce demographics, and changing employee expectations are the main factors influencing HR strategies. Key findings include: (1) adoption of AI and big data technologies in the recruitment and selection process, (2) increased focus on work flexibility and work-life balance, (3) transformation of employee development programs towards a continuous learning and personalization model, (4) shift from traditional performance management to a more agile and real-time feedback-based approach, and (5) the importance of building an inclusive and adaptive organizational culture. The study also uncovers the ethical and social challenges that arise from the digitalization of HR practices, as well as the importance of bridging the digital divide in the workforce. In conclusion, successful organizations are those that are able to adapt their HR strategies to meet the challenges of the digital era, while maintaining a focus on the human factor as the core of effective HR management.